Comparison of the Effectiveness of Acceptance and Commitment–Based Couple Therapy and Cognitive–Behavioral Couple Therapy on Cognitive Distortions, Emotion Regulation, and Emotional Intimacy in Couples Experiencing Marital Disenchantment - Haji Abbasi, Azin; Karbalai Herofteh, Fatemehsoghra; Sanagouye Moharer, Gholamreza (Applied Family Therapy Journal (AFTJ), 2026)
Objective: This study aimed to compare the effectiveness of acceptance and commitment–based couple therapy and cognitive–behavioral couple therapy on interpersonal cognitive distortions, emotion regulation strategies, and emotional intimacy in couples experiencing marital disenchantment. Methods and Materials: The study employed a quasi-experimental design with pretest, posttest, and three-month follow-up assessments and a control group. The statistical population consisted of couples aged 20–40 years who sought counseling for marital disenchantment in Tehran in 2023. Using purposive sampling and based on inclusion and exclusion criteria, 45 couples were selected and randomly assigned to two experimental groups and one control group. The first experimental group received acceptance and commitment–based couple therapy, and the second experimental group received cognitive–behavioral couple therapy, each delivered in 12 sessions of 90 minutes over three months, while the control group remained on a waiting list. Data were collected using standardized questionnaires measuring interpersonal cognitive distortions, emotion regulation strategies (cognitive reappraisal and suppression), and emotional intimacy at three time points. Data analysis was conducted using repeated-measures analysis of variance and Bonferroni post hoc tests. Findings: The results of repeated-measures analysis of variance indicated significant group × time interaction effects for all components and the total score of cognitive distortions, emotion regulation strategies, and emotional intimacy. Acceptance and commitment–based couple therapy produced significantly greater reductions in rejection in relationships, misperception, and total cognitive distortions compared with cognitive–behavioral couple therapy. Additionally, acceptance and commitment–based couple therapy led to a significantly greater increase in cognitive reappraisal and a greater reduction in emotion suppression. Emotional intimacy increased significantly in both experimental groups compared with the control group; however, the increase was significantly greater in the acceptance and commitment–based couple therapy group. These effects remained stable at the three-month follow-up. Conclusion: Acceptance and commitment–based couple therapy was more effective than cognitive–behavioral couple therapy in reducing interpersonal cognitive distortions, improving emotion regulation strategies, and enhancing emotional intimacy in couples experiencing marital disenchantment, suggesting its particular suitability for interventions targeting emotional disengagement and cognitive rigidity in distressed marital relationships.